2002
DOI: 10.1111/j.1151-2916.2002.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Step‐Energy Barriers and Particle Shape Changes during Coarsening

Abstract: Models of particle shape changes usually do not account for the step-energy barrier associated with adding or removing additional atomic planes from a faceted surface. However, the step-energy barrier can be a substantial limitation when the free energy changes that drive particle shape changes are relatively low. A good example of this is particle coarsening. The analysis presented in this article describes dislocation-free particles with surfaces that have faceted and nonfaceted regions. When the chemical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…When the step free energy is <1.0 × h γ, the shape of the grain is a round‐edged polyhedron. The growth of round‐edged polyhedral grains, however, is also governed by the growth of facets, as shown in recent studies 21–23 …”
Section: Theoretical Background: Prediction Of Grain Growth Behaviormentioning
confidence: 81%
“…When the step free energy is <1.0 × h γ, the shape of the grain is a round‐edged polyhedron. The growth of round‐edged polyhedral grains, however, is also governed by the growth of facets, as shown in recent studies 21–23 …”
Section: Theoretical Background: Prediction Of Grain Growth Behaviormentioning
confidence: 81%
“…. In solid/liquid two‐phase systems, theoretical and experimental studies suggested that the growth of partially faceted grains is governed by the migration of facets.…”
Section: Microstructure Evolution In Polycrystals: Model and Principlementioning
confidence: 99%
“…13 Also relevant are characteristic EhrlichSchwoebel type lengths associated with additional barriers to round kinks and corners in 2D and to cross step edges and move between facets in 3D. 10,14,15 In general, key exponents describing both temporal scaling and size-scaling of relaxation times differ from macroscale theory. [1][2][3]5,6 Note also that reshaping of 2D epitaxial clusters and pits, or 3D clusters and voids in bulk crystals, is equivalent on the macroscale, 16 but not on the nanoscale.…”
mentioning
confidence: 99%